2018
DOI: 10.3136/fstr.24.493
|View full text |Cite
|
Sign up to set email alerts
|

Production of Isoflavone Aglycone-enriched Tempeh with <i>Rhizopus stolonifer</i>

Abstract: The regional standard for tempeh recently established by the Codex Alimentarius defines the use of Rhizopus oligosporus, Rhizopus oryzae, and/or Rhizopus stolonifer as soybean tempeh starters. However, there has been little comparative study on the tempeh prepared with these Rhizopus species. This study compared the contents and compositions of isoflavones in tempeh prepared with these Rhizopus species. The contents of total isoflavone aglycones (daidzein and genistein) and the ratio of total aglycones to tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…These results indicated that the amount of these metabolites increased as mycelia formed throughout tempe fermentation, regardless of the soaking conditions. This coincided with previous reports of increased isoflavones [18] and amino acids [19] during tempe fermentation. The metabolites of arabitol, n-propylamine, glucono-1,5-lactone, malonic acid, sorbose, gluconic acid, fructose, psicose, and tagatose were located on the negative side of PC1, indicating decreasing quantities as tempe fermented.…”
Section: Metabolite Profiles Of Tempe With and Without Soaking In Vinegar Over Timesupporting
confidence: 93%
“…These results indicated that the amount of these metabolites increased as mycelia formed throughout tempe fermentation, regardless of the soaking conditions. This coincided with previous reports of increased isoflavones [18] and amino acids [19] during tempe fermentation. The metabolites of arabitol, n-propylamine, glucono-1,5-lactone, malonic acid, sorbose, gluconic acid, fructose, psicose, and tagatose were located on the negative side of PC1, indicating decreasing quantities as tempe fermented.…”
Section: Metabolite Profiles Of Tempe With and Without Soaking In Vinegar Over Timesupporting
confidence: 93%
“…Rhizopus stolonifer increased daidzein and genistein levels more than R. oligosporus and R. oryzae by up to twofold (Kameda, Aoki, Yanaka, Kumrungsee, & Kato, 2018). In rats fed with a high鈥恌at diet, only supplementation of tempeh fermented with R. stolonifer improved liver function by significantly suppressing serum aspartate transaminase, total bilirubin, and ammonium levels (Kameda et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Tempeh (F3) had a similar H-ORAC value as rice miso and barley miso, but lower than that of natto (Figure 2). 尾-Glucosidase produced by Rhizopus filamentous fungi, which is used for tempeh fermentation, hydrolyzes isoflavone glycosides into aglycones [Kameda et al, 2018]. It was suggested that the isoflavone aglycone produced during fermentation might contribute to the antioxidant properties of tempeh [Murakami et al, 1984].…”
Section: Peroxyl Radical Scavenging Capacity Of Fermented Soybean Foodmentioning
confidence: 99%
“…These soyfoods, e.g. miso [Matsuo & Hitomi, 2007], soy sauce [Long et al, 2000], natto [Ping et al, 2012], and tempeh [Chang et al, 2009;Kameda et al, 2018], have also been reported as a source of natural antioxidants. The thermal processes, as well as pressurization and fermentation are used to obtain soyfoods.…”
Section: Introductionmentioning
confidence: 99%